(untitled) - Biron, Paul J (Washington, D.C, 1985)
This glossary presents English - French and French - English terminology related to water supply (investigation, production, distribution), environmental sanitation, and health education. [Le présent glossaire Anglais - Francais regroupe des termes concernant l'approvisionnement en eau (recherce, production, distribution), l'assainissement du milieu et l'éducation sanitaire.]
Keywords: english language,french language,sanitary engineering,water supply engineering; dictionaries,dictionaries,dictionaries,dictionaries; french,english